Precipitation, Sea Surface Temperature Anomaly (SSTA) and Savanna Fire in Waingapu - Erianto Indra Putra; Abi Abdillah Niko Ghaniyy (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Waingapu is one of the areas in Nusa Tenggara Timur Province which often suffered from savanna fires. Savanna fires prevention can be done by utilizing hotspot data for analysis using Geographic Information System (GIS). The climate is one of factors influence the occurrence of savanna fires in Waingapu. The purpose of this study was to analyze the relationship between precipitation, SST anomalies, and the occurrences of savanna fires in Waingapu. This research was conducted on February April 2021 at the Forest and Land Fires Laboratory, Department of Silviculture, Faculty of Forestry and Environment, IPB University. The data used are MODIS and VIIRS hotspot data, daily precipitation data and SST 3.4 anomaly data. The results showed that precipitation was inversely related to hotspots with a negative correlation value. SST anomaly is inversely related to precipitation a negative correlation value. While the SST anomaly with hotspots is directly proportional with a positive correlation value. Keywords: climate, hotspot, Geographic Information System (GIS), Waingapu